1-{[4′-(1H-1,2,4-Triazol-2-ium-1-ylmethyl)biphenyl-4-yl]methyl}-1H-1,2,4-triazol-2-ium bis(3-carboxy-5-iodobenzoate)–5-iodobenzene-3,5-dicarboxylic acid–water (1/2/2) - Zhang, Kou-Lin; Deng, Ye; Ng, Seik Weng (International Union of Crystallography, 2012)
The neutral carb-oxy-lic acid molecule and the carboxylate anion in the title compound, C18H18N6 2+· 2C8H4IO4 -·2C 8H5IO4·2H2O, are both nearly planar (r.m.s. deviations = 0.034 and 0.045 Å, respectively). In the cation, the mid-point of the C - C bond linking the two benzene rings lies on a center of inversion, and the triazole ring is approximately perpendicular to the adjacent benzene ring [dihedral angle = 83.2 (3)°]. In the crystal, the cations, anions, carb-oxy-lic acid and lattice water molecules are linked by N - H⋯O, O - H⋯N and O - H⋯O hydrogen bonds, generating a ribbon running along [1-10]. The crystal studied was a non-merohedral twin with the components in a 51.2 (1):48.8 (1) ratio. © Zhang et al. 2012.